2021
DOI: 10.3889/oamjms.2021.7693
|View full text |Cite
|
Sign up to set email alerts
|

Community Knowledge and Attitudes about the Transmission of Dengue Haemorrhagic Fever and Its Relationship to Prevention Behaviour in Palembang, South Sumatra, Indonesia

Abstract: BACKGROUND: PSN 3 M Plus is a long-running program in Indonesia for the prevention and control of dengue hemorrhagic fever (DHF). AIM: This study aimed to determine the knowledge, behavior, attitudes, and beliefs of the community toward PSN 3 M Plus in preventing and controlling the spread of DHF. METHODS: A cluster random sampling method was used to recruit 200 respondents in endemic areas and 100 respondents in sporadic locations of Indonesia from August 2020 to February 2021. The respondents were interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In contrast to the above findings, a study conducted in Thailand, taking the climate data and dengue data during the period from 1982 -2018 revealed that there is no statistically significant relationship between dengue cases and sunshine duration (Noppradit et al, 2021). This is supported by a study done in Indonesia which has shown a non-statistically significant weak relationship between sunshine and dengue cases (r = 0.008; p = 0.865) (Minarti et al, 2021). According to Noppradit et al, 2021, there is no significant association between sunshine and dengue (Noppradit et al, 2021).…”
Section: Impact Of Sunshine On Denguementioning
confidence: 84%
See 3 more Smart Citations
“…In contrast to the above findings, a study conducted in Thailand, taking the climate data and dengue data during the period from 1982 -2018 revealed that there is no statistically significant relationship between dengue cases and sunshine duration (Noppradit et al, 2021). This is supported by a study done in Indonesia which has shown a non-statistically significant weak relationship between sunshine and dengue cases (r = 0.008; p = 0.865) (Minarti et al, 2021). According to Noppradit et al, 2021, there is no significant association between sunshine and dengue (Noppradit et al, 2021).…”
Section: Impact Of Sunshine On Denguementioning
confidence: 84%
“…Further a study conducted in Indonesia has revealed that there is a strong correlation between wind speed and DHF incidence (r = 0.76). However, this finding has found to be statistically not significant (r= 0.76, p=0.492) (Minarti et al, 2021). Apart from the above findings, five studies included in the review have concluded that there is no correlation between wind speed and DHF incidence or dengue cases (Arsin et al, 2020;Harumy & Ginting, 2021;Noppradit et al, 2021;S.…”
Section: Impact Of Wind On Denguementioning
confidence: 92%
See 2 more Smart Citations
“…However, the local people need to have a sufficient understanding of the routes of dengue virus transmission, as their behaviour plays a vital role in limiting dengue disease transmission. 13 This study aimed to determine the knowledge, attitude, and compliance with the management of PSN 3M Plus strategies of those living in Surabaya. Study findings of this research are expected to help policymakers develop strategies for more effective prevention and control of dengue virus infection and increase community participation in dengue prevention programs.…”
Section: Introductionmentioning
confidence: 99%